The Influence Of Service Quality And Product Quality Of Mobile Banking On Customer Satisfaction - Ayu Liring Bethari; Aslamia Rosa; Ahmad Maulana; Zakaria Wahab (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to analyze the effect of service quality and product quality of mobile banking on customer satisfaction of Bank Sumsel Babel. This quantitative research uses data from 123 mobile banking customer respondents in the Palembang area collected through an online questionnaire during May to June 2024. Multiple linear regression analysis with SPSS version 26 was used to test the hypothesis. The results showed that both service quality and product quality had a positive and significant effect on customer satisfaction, and simultaneously also had a significant effect. Product quality has a more dominant influence on customer satisfaction than service quality